2012
DOI: 10.1002/jcp.24231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute exercise over heart proteome from monogenic obese (ob/ob) mice

Abstract: Exercise is recognized to prevent and attenuate several metabolic and cardiovascular disorders. Obesity is commonly related to cardiovascular diseases, frequently resulting in heart failure and death. To elucidate the effects of acute exercise in heart tissue from obese animals, 12-week-old C57BL6/J obese (ob/ob) and non-obese (ob/OB) mice were submitted to a single bout of swimming and had their hearts analyzed by proteomic techniques. Mice were divided into three groups: control (ob/ob, n = 3; ob/OB, n = 3);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
(71 reference statements)
2
13
0
Order By: Relevance
“…Myocyte fibrosis and impairment contractility affects the Ca 2+ -dependent cross-bridge interaction with actin, influencing the progression of hypertensive LVH to HF. Differentially, hypertrophy induced by exercise improves force and contraction regulators, leading to positive cardiac adaptations [13,28,30]. In contrast to the down-regulation of myosin light chain 1 observed in LV in SHR [67], the abundance of proteins related to force regulation (myosin light chain 4) and thin filament structure (tropomyosin beta and alpha chains 1,2, 3, and troponin T) was enhanced by both training intensities (Fig.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Myocyte fibrosis and impairment contractility affects the Ca 2+ -dependent cross-bridge interaction with actin, influencing the progression of hypertensive LVH to HF. Differentially, hypertrophy induced by exercise improves force and contraction regulators, leading to positive cardiac adaptations [13,28,30]. In contrast to the down-regulation of myosin light chain 1 observed in LV in SHR [67], the abundance of proteins related to force regulation (myosin light chain 4) and thin filament structure (tropomyosin beta and alpha chains 1,2, 3, and troponin T) was enhanced by both training intensities (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…Despite the large body of heart proteome research in response to a number of diseases, little research has been conducted in response to exercise stimulus on the nonpathologic heart [28][29][30][31][32] and even less on pathologic conditions such as ischemic insult [33], infarction [34], and obesity [13]. Although the majority of these data are gathered by gel-based techniques, LC-MS methods are the most up-to-date, being used as qualitative and quantitative analytical approaches to complement gel-based methods and considerably enhance proteomic data [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, absence of folate (i) increased abundance of Ppa1 that contributes to ATPase activity in oxidative phosphorylation and, (ii) decreased abundance of Nme2 that is essential to the synthesis of nucleoside triphosphates other than ATP. The latter change has been associated with cardiac contractile dysfunction (Petriz et al, 2013). Second, MD deficiency decreased the abundances of mitochondrial Etfa, an electron acceptor for transfer to the respiratory chain, and Glud1 that catalyzes oxidative deamination of glutamine into ˛-ketoglutarate (Zhang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Further research in LV proteome showed that moderate treadmill running led to diverse alteration in the contractile, stress-related, and metabolic function of cardiac proteins, where heart fatty acid binding proteins (HFABP), thioesterase-1, and short-chain acyl-CoA dehydrogenase were upregulated [98]. Moreover, one single bout of high intensity swimming at moderate and high intensity was also shown to modulate LV proteins from obese (ob/ob) and control nonobese mice (ob/OB) [100]. However, in this study, HFABP was downregulated after high intensity exercise in nonobese mice but not in obese mice.…”
Section: Does Exercise Extenuate Cardiac Pathological Hypertrophy?mentioning
confidence: 99%